Prevalence of comorbidities among patients with rheumatoid arthritis in the UAE: a case–control study - Jamal Al-Saleh; Naureen Ali Khan; Noura Zamani; Hend AlSaidi; Wafae Rachidi (BMJ Open)
Objectives Data on the rate of comorbidities in Arab patients with rheumatoid arthritis (RA) are limited, and extrapolating the prevalence of comorbidities from international studies is challenging. This study aimed to investigate the prevalence of comorbidities in patients with RA, compare it with that in non-RA controls and explore the association between the body mass index of patients with RA and comorbidities.Design This is a retrospective, case–control study.Setting This study included patients receiving secondary care at the Rheumatology Department of a public hospital in the Emirate of Dubai. The controls were recruited from patients receiving primary and secondary care at the Dubai Academic Health Corporation in the fourth quarter of 2022.Participants This study included all consecutive UAE national patients with RA who visited the rheumatology clinic. The study included 1756 participants in an age-matched and sex-matched control group and 439 patients with RA. Of these, 88.6% were female, and the median age was 55 years. Each RA case was randomly matched with four controls of the same age and sex. All relevant information, including case and control demographics and comorbidities, was retrieved from the electronic medical record.Primary and secondary outcome measures The relative risk of comorbidities was compared between patients with RA and age-matched controls. The relationship between obesity in RA and the frequency of comorbidities was determined.Results This study revealed that 188 (42.8%) patients with RA had at least one comorbidity, whereas only 636 (36.2%) individuals in the control group had at least one comorbidity (OR 1.3; 95% CI 1.1 to 1.6, p<0.01). Patients with RA were more likely to have ischaemic heart disease (OR 3.9; 95% CI 2.3 to 6.6, p<0.0001), fibromyalgia (OR 25; 95% CI 13 to 34, p<0.0001), cataract (OR 5.8; 95% CI 4 to 8.5, p<0.0001), osteoporosis (OR 6.8; 95% CI 4.6 to 10, p<0.0001) and knee osteoarthritis (OR 6.1; 95% CI 4.8 to 7.8, p<0.0001).Conclusions Patients with RA were more likely to have cardiovascular, pulmonary and musculoskeletal comorbidities compared with the control group. Obese patients with RA had a higher incidence of comorbidity than non-obese patients with RA.